Study of Relaxations in Epoxy/Rubber Composites by Thermally Stimulated Depolarization Current and Dielectric Spectroscopy - Wang, Chuang; Zhou, Gang; Zhu, Weiyu; Chen, Chi; Fu, Yuwei; Zhang, Zaiqin; Li, Hui (Frontiers in Chemistry, 2022)
Liquid rubber toughened epoxy resins are widely used in electrical equipment and electronic packaging. Previous studies have only investigated the relaxation process of epoxy resins through dielectric spectroscopy. The trap characteristics of the relaxation process by thermally stimulated depolarization current (TSDC) analysis are less studied. In this work, TSDC and broadband dielectric spectroscopy techniques were used to complementarily characterize the dielectric relaxation process of hydroxyl-terminated liquid nitrile-butadiene rubber (HTBN) toughened epoxy resin polymers. The experimental results show that HTBN introduces two new relaxation processes in the epoxy matrix, which are attributed to the α polarization of the rubber molecule and the interfacial polarization based on the correlation between the TSDC and the dielectric spectroscopy data, respectively. The trap parameters of each TSDC current peak were obtained using the multi-peak fitting method. The addition of rubber increases the trap density in epoxy composites significantly, especially for traps with energy levels in the range of 0.5 eV to 0.9 eV. The trap energy level of the DC conductivity process increases with increasing rubber concentration. The above results provide analytical ideas for rubber-toughened epoxy resins' polarization and trap characteristics and theoretical guidance for formulation improvement.